Reference values for left ventricular strain using 2-dimensional speckle tracking in primary school-aged healthy Egyptian children - Shaimaa A Habib; Ghada M.S Ahmad; Layla A Mohamed; Ragaa A Mohamed (Wolters Kluwer Medknow Publications, 2019)
Background The aim was to set normal values of two-dimensional speckle-tracking echocardiography (2D-STE)-derived left ventricular strain is a prerequisite for its routine clinical application in children. The aim of this study was to establish our values of LV systolic strain using 2D-STE in a large cohort of primary school-aged healthy Egyptian children. Participants and methods All studied cases underwent complete physical examination, including anthropometric, heart rate, and blood pressure measurements. Transthoracic echocardiography was acquired in 420 healthy participants, including routine echocardiography study, and tissue Doppler imaging and 2D-STE were performed. Global longitudinal strain (GLS), global circumferential strain (GCS), and global radial strain (GRS) values were determined. Multiple linear regression was performed to define the strongest predictors for GLS, GCS, and GRS. Results A total of 420 children were included, with a mean age of 9.39±1.98 years. GCS values were −33.97±8.86% at the mitral valve and −33.88±8.59% at papillary muscle (PM). GLS values were −21.6±2.59% in apical four-chamber, −21.96±2.34% in apical two-chamber, and −22.17 ±2.58% in apical three-chamber views, whereas the GRS values were 46.34±10.05 at mitral valve and 46.37±9.97 at PM. Further analysis showed that the age was the strongest predictor of GRS and GCS (B=−2.018 and 2.47, respectively, and P<0.001 for both), whereas DBP was the strongest predictor of GLS (R2=0.048, P<0.001). Conclusion This is the first Egyptian report that defines normal reference values for myocardial strain in longitudinal, circumferential, and radial directions assessed using 2DSTE imaging in a large pediatric cohort. There is a need to use age-specific reference values for the adequate interpretation of 2DSTE measurement.